2016
DOI: 10.1159/000444879
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Disturbances in Premenopausal Women with End-Stage Renal Disease: A Cross-Sectional Study

Abstract: Objective: To evaluate menstrual disturbances and sex hormonal status in premenopausal women with end-stage renal disease (ESRD). Subjects and Methods: The study consisted of 184 patients with ESRD treated with one of four treatment modalities (46/modality): conventional hemodialysis (CHD), continuous ambulatory peritoneal dialysis (CAPD), nocturnal hemodialysis (NHD) and renal transplantation (RT). Blood samples were collected to determine sex hormone levels. Sociodemographic and clinical data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Once reaching end-stage disease, most women are anovulatory, even if regular menstruation is present [2], as uremia leads to dysregulation of the hypothalamic-pituitary-gonadal axis. Follicular stimulating hormone levels are similar to non-uremic women, but luteinizing hormone (LH) levels are elevated.…”
Section: Fertility and Esrdmentioning
confidence: 99%
“…Once reaching end-stage disease, most women are anovulatory, even if regular menstruation is present [2], as uremia leads to dysregulation of the hypothalamic-pituitary-gonadal axis. Follicular stimulating hormone levels are similar to non-uremic women, but luteinizing hormone (LH) levels are elevated.…”
Section: Fertility and Esrdmentioning
confidence: 99%
“…To reference only a few studies, menstrual disturbances are reported to occur in the range of 64.2% (of 165) [ 51 ], 73% (of 63) [ 52 ], 74% (of 39) [ 53 ], and 80% (of 25) [ 54 ] of premenopausal patients after the initiation of dialysis. Of these, Lin et al [ 51 ] has documented the largest cohort of 165. The most common disturbance is secondary amenorrhea [ 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Menstrual disorders have been shown to affect 64.2% of women with chronic renal disease [4]. The prevalence of HMB is 22.9%$38.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CRF is $200 cases per one million people in Western countries [3]. CRF in women is frequently accompanied by disturbances to endocrine function, leading to menstrual disorders that occur in 64.2% of women with CRF [4]. Uncontrolled HMB is a significant problem in subjects with chronic anemia due to renal disease as it leads to aggravation or worsening of the anemia.…”
Section: Introductionmentioning
confidence: 99%